Presenting Japanese Buddhism to the West : Orientalism, Occidentalism, and the Columbian exposition - Snodgrass, Judith (University of North Carolina Press, 2003)
Japanese Buddhism was introduced to the West during the World's Parliament of Religions, in the 1893 Columbian Exposition. In describing and analysing this event, this text challenges the view of Orientalism as a one-way process by which Asian cultures are understood through Western ideas.